Experimental investigation of the velocity-dependent relative permeability andsweep efficiency of supercritical CO2 injection into gas condensate reservoirs - Al-Abri, Abdullah; Sidiq, Hiwa; Amin, Robert (Elsevier, 2009)
This paper presents a laboratory investigation of the velocity-dependent relative permeability (VDRP) and recovery efficiency of supercritical CO2 injection into gas condensate reservoirs for enhanced recovery purposes. A high pressure high temperature coreflood facility was commissioned to duplicate reservoir conditions and to conduct two systematic investigation lines of displacement tests on sandstone cores with varying injection velocities of 10, 7, 5, 2 and 1 cm/hr; equivalent to typical field interstitial velocities of around 8, 5.5, 4, 1.6 and 0.8 ft/day. One unsteady-state displacement procedure was used to displace dead condensate with SCCO2 at 95 oC while the other set simulates SCCO2 injection to sweep natural gas at 160 oC. These measurements form a single element of an extensive enhanced oil recovery project for a field in Western Australasia. The coreflooding results indicate that slower displacement flow rates (i.e. representative of flow behaviours deep in reservoirs or low injection rates) yield greater condensate ultimate recovery (13.93% OOIP total difference). This negative velocity coupling leads also to delayed gas breakthrough (0.16 PVI total difference compared to 10 cm/hr BT). These experimental observations benchmark existing simulation studies 6,12. The natural gas displacements by SCCO2, however, interestingly, show an opposite response.Faster displacement rates demotivate diffusion and dispersion of gases and thus yield a better sweep efficiency and later breakthrough (SCCO2 breaks at effluent around four times later at 10 cm/hr compared to 1 cm/hr). This positive velocity coupling improves relative permeability data (around 80% increase in relative permeability at 10 cm/hr compared to that at 1 cm/hr). Although the need for an accelerated hydrocarbons production to meet market demands may stimulate the use of higher SCCO2 injection rates there will, however, be a tradeoff between incremental methane recovery and the produced condensate sweep efficiency. This work serves as a 'building-block' to the essential practical understanding of the displacement flow rates associated with improved natural gas and condensate recovery by SCCO2 injection.